2021
DOI: 10.1017/spq.2021.14
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Pandemics: The Effect of Stay-At-Home Orders on COVID-19 Mitigation

Abstract: The COVID-19 pandemic has upended every aspect of American life. State governments responded quickly to protect public health and stabilize overwhelmed hospital systems. The most restrictive policy, the stay-at-home order, was seen by public health officials as a cornerstone of successful state mitigation strategies. But like many aspects of contemporary politics, support for these efforts took on a distinctly partisan hue. In this paper, I argue that party politics significantly affected state policy response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Although not examined here, political disposition has played an important role in both implementation of COVID-19 mitigation measures 37–39 and their compliance. 40–42 This body of evidence has shown that conservatives and liberals respond differently to the COVID-19 pandemic such that conservatives are less likely to adopt recommended behavior changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not examined here, political disposition has played an important role in both implementation of COVID-19 mitigation measures 37–39 and their compliance. 40–42 This body of evidence has shown that conservatives and liberals respond differently to the COVID-19 pandemic such that conservatives are less likely to adopt recommended behavior changes.…”
Section: Discussionmentioning
confidence: 99%
“…Decision makers may consider adopting comprehensive communication strategies to inform populations about COVID-19 risks, adopted interventions, and why adherence to mitigation strategies is critical, which have been shown to be effective in increasing compliance across various settings. 35,36 Although not examined here, political disposition has played an important role in both implementation of COVID-19 mitigation measures [37][38][39] and their compliance. [40][41][42] This body of evidence has shown that conservatives and liberals respond differently to the COVID-19 pandemic such that conservatives are less likely to adopt recommended behavior changes.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, media coverage has been documenting a similar phenomenon amongst parent groups organizing – many of whom align with ideologically conservative political campaigns. 2 There is also evidence that partisan control played a significant role in different emergency response policy: stay-at-home orders (Patterson, 2020). Again, while low in volume, there is a consistent trend in that political factors play a heavy role in policy decision-making around school reopening.…”
Section: The Politics Of School Reopening During the Covid-19 Pandemicmentioning
confidence: 99%
“…At the local level, policy imitation was recognized as influencing "stay-at-home" orders. Since the different policies are untested, governments copy each other in order to obtain the best solutions (Patterson, 2021).…”
Section: Creeping Crisis Emergency Managementmentioning
confidence: 99%